PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP KEMAMPUAN KONEKSI MATEMATIK SISWA - Yenti, Fepryna (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2018)
Mathematics learning process that is still centered on the teacher caused the low ability of mathematical connections of students in grade VIII SMPN 1 Baso. This study aims to determine whether the mathematical connection ability of students using Contextual Teaching and Learning (CTL) learning model is better than the mathematical connection ability of students using conventional learning. The type of this research is experimental research with Randomized control group only design. The population in this study is the students of class VIII SMPN 1 Baso consisting of seven classes. Samples taken from the population were taken by Random Sampling technique. The selected sample is class VIII4 as the experimental class and class VIII3 as the control class. Data analysis technique using t test. The result of tcalculation = 7,18 and ttable = 1,679, because tcount> ttable concluded that the mathematical connection ability of students using Contextual Teaching and Learning (CTL) learning model is better than the students' mathematical connection ability using conventional learning in grade VIII SMPN 1 Baso Lesson Year 2017/2018